1988
DOI: 10.1002/cm.970100113
|View full text |Cite
|
Sign up to set email alerts
|

Actin polymerization and pseudopod extension during amoeboid chemotaxis

Abstract: Amoebae of the cellular slime mold Dictyostelium discoideum are an excellent model system for the study of amoeboid chemotaxis. These cells can be studied as a homogeneous population whose response to chemotactic stimulation is sufficiently synchronous to permit the correlation of the changes in cell shape and biochemical events during chemotaxis. Having demonstrated this synchrony of response, we show that actin polymerization occurs in two stages during stimulation with chemoattractants. The assembly of F-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 69 publications
6
64
0
Order By: Relevance
“…Also, in the case of a step-like increase in the extracellular cAMP concentration, a nonmonotonic response was observed for the averaged signal (data shown in Supporting Information). However, compared with the pulse response, the initial cytosolic depletion was prolonged by several seconds and was succeeded by a more strongly delayed second cycle, in agreement with previous observations (5,6,8,9).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Also, in the case of a step-like increase in the extracellular cAMP concentration, a nonmonotonic response was observed for the averaged signal (data shown in Supporting Information). However, compared with the pulse response, the initial cytosolic depletion was prolonged by several seconds and was succeeded by a more strongly delayed second cycle, in agreement with previous observations (5,6,8,9).…”
Section: Resultssupporting
confidence: 91%
“…Between 5 and 10 s after the stimulus, a first maximum in the filamentous actin content is observed, followed by a second, less intense but prolonged maximum that starts about 30 s after the stimulus and can last for several minutes (8,9). The first rapid response of this biphasic time profile is generally associated with decreasing motility and rounding up of the cell, while the prolonged second phase is attributed to the generation of new localized pseudopods (9). Numerous later studies, including live-cell fluorescence imaging, have confirmed this behavior for Dictyostelium (10-12).…”
mentioning
confidence: 99%
“…Interestingly, in Dictyostelium, the kinetics of chemoattractantinduced RacB activation, PtdIns(3,4,5)P 3 production and F-actin polymerization all share a similar biphasic profile, namely a strong and rapid first peak at about 5 s after chemoattractant stimulation, followed by a second, lower, but much broader, peak at about 30-60 s [35,69,[89][90][91]. The first rapid response was suggested to represent the turning 'on' of the signal-transduction machinery, whereas the second slower response, which most likely results from positive-feedback signalling, was linked to pseudopod extension [29,35,[89][90][91][92]. In addition, the second phase of cAMP-induced RacB activation, as well as F-actin polymerization, were found to be sensitive to perturbations in PI3K activity (reduced in pi3k1/2-null cells or cells treated with LY294002, and increased in pten − cells), suggesting that they are both regulated by PtdIns(3,4,5)P 3 [35,69].…”
Section: Figure 3 Small Gtpases Similarly Regulate Actin and Myosin Dmentioning
confidence: 99%
“…The cytoskeletons composed of actin and myosin II change rapidly during these events (21,28), and this system is particularly suitable for the study of the rapid reorganization of cytoskeletons as the result of external stimulation. The amount of actin accumulated in detergent-insoluble cytoskeletons increases at 3-5 sec or at 5-10 sec (the first peak; the timing of which has been variously reported by different investigators) and 25-45 sec after the addition of CAMP.A similar response of actin is induced in vegetative cells after the addition of folic acid (5,16,17). The first peak of actin may represent the polymerization of actin that is mediated by the release of capping protein from the barbed end of F-actin (10).…”
mentioning
confidence: 61%